Detection of Foreign Material in Soybean (Glycine max) Grain - Schwartz-Lazaro, Lauren M.; LaBiche, Gabrielle; Copes, Josh T. (Frontiers in Agronomy, 2022)
The United States (US) is ranked second in the world in exporting soybean with Louisiana ranked 17th for exporting agricultural products, including soybean. Importing countries maintain high standards for the level of foreign material (FM) accepted in soybean grain shipments. While it has been identified that changes are needed, there is limited research on what comprises the FM, specifically weed seeds, in these samples. The objective of the study was to determine what proportion of the FM consists of weed seeds and to quantify those seeds in Louisiana grain elevators and in Mississippi River Valley (MRV) barges bound for Louisiana. Fifty soybean samples were taken from barges traveling down the Mississippi River Valley (MRV) as well as 56 total samples from Louisiana grain elevators. Each sample was weighed, and each fraction of the FM was separated, weighed, and counted to determine the exact proportion of each fraction. Twelve different weed seeds were found within the FM samples. The amount of weed seeds found was not consistent based on where the sample was retrieved, grain elevator or MRV barge, however the total FM was <1% for all MRV barge samples. A better understanding of the FM in soybean grain samples will allow the midsouthern US to know more accurately which weed seeds are found within grain bound for exportation.